Association between duration of visual symptoms and early postoperative visual outcome following pituitary macroadenoma surgery (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Pituitary tumors represent approximately 10-17% of intracranial tumors. However, they may grow large and extend into surrounding structures, resulting in neurological and hormonal complications, including visual impairment. The duration of visual involvement will help predict visual outcomes after pituitary surgery and will be helpful for patient counseling.Methodology: A prospective observational study was conducted in the neurosurgery department of Bangabandhu Sheikh Mujib Medical University (BSMMU). The patient who fulfilled the selection criteria, which included [specific criteria], was enrolled in this study and was divided into two groups according to the Duration of visual symptoms. A total of 24 patients were selected; 12 presented with visual symptoms with less than six months duration; they were included in the first group, and 12 patients with more than 6 months duration were included in the second group. Patient data were recorded in a predetermined data sheet. An ophthalmologist examined visual status. Data was processed and analyzed using SPSS version 22. An appropriate statistical test for data analysis (Chi-square test and student t-test) was performed. Statistical significance was at P-value